BIODIVERSITY AND PARTICIPATORY CONSERVATION OF PEAT SWAMP FORESTS AT SIMUNJAN FOREST RESERVE, SARAWAK SUSTAINABLE UTILISATION OF PEATLAND AND HAZE MITIGATION IN ASEAN (SUPA) - Micky, Vincent (Forest Department Sarawak and Universiti Malaysia Sarawak, 2024)
Simunjan Forest Reserve, which is part of the Permanent Forest Estates (PFEs), is a remnant peat swamp forest that is surrounded mostly by oil palm plantations. There are settlements and villages surrounding the forest reserve, and a general survey indicates that the local communities in the Simunjan Forest Reserve vicinity are mainly from the Malay and Iban communities. Currently, there is no proper baseline data for the biological and non-biological resources for Simunjan Forest Reserve. Therefore, this project was conducted to document a biodiversity inventory for the peat swamp forests at Simunjan Forest Reserve, to engage the participation of the local communities including opportunities for participation of women folks in peat swamp conservation effort and to develop a conservation plan for Simunjan Forest Reserve.